Probiotic and Anthocyanin Rich Purple Sweet Potato Frozen Yogurt - C. Pradeepika; Mariya Shoji; J. Sreekumar; T. Krishnakumar; M.S. Sajeev; C. Visalakshi Chandra; K. Hanume Gowda; Kalidas Pati (JOURNAL OF ROOT CROPS, 2024)
Sweet potatoes are a rich source of diverse bioactive compounds, essential minerals, and dietary fibre and can be rationally targeted for wider human health-focused dietary solutions, especially to address diet-linked non-communicable chronic disease challenges. Therefore, the development of probiotic and anthocyanin-rich purple-fleshed sweet potato-based frozen yogurt to preserve and improve sweet potato-based human health-relevant nutritional qualities for health-targeted food application was studied. Purple fleshed sweet potato (PSP) variety Bhu Krishna was selected based on its high baseline phenolic content and antioxidant activity. Full factorial design with five levels of PSP puree and yogurt resulted in 25 experimental runs employed in this study. Nutritional and microbial data of frozen yogurt was recorded before storage and 10thday of storage at -4°C. Among 25 combinations frozen yogurt samples with a higher percentage of PSP showed significantly (p<0.05) higher nutritional value. The combination, 70:30 showed higher anthocyanin content of 55.24 and 51.14 mg100 g-1, protein content of 6.56 and 5.64%, and a fibre content of 0.69 and 0.33% on zero and tenth day of storage. In addition, the viable beneficial microbial count of formulations was ranged between 5.45 to 7.22 log CFU ml-1 at tenth day of storage. Results suggested that beneficial lactobacillus (LAB) based frozen yogurt development was an effective post-harvest processing strategy for higher retention of anthocyanin content and its associated antioxidant and anti-hyperglycaemic functionalities in sweet potatoes. Additionally, such frozen yogurt with probiotic as well as prebiotic potential can be integrated into health-focused dietary solution strategies, especially to improve human gut health and to mitigate chronic oxidative stress-linked non-communicable disease challenges. Keywords : Frozen yogurt, Purple sweet potato, Probiotic, Viable cell count, Anthocyanins